Decline in Feeding Activity of Female Cultured Delta Smelt Prior to Spawning. (27th March 2014) - Hung, Tien‐Chieh; Eder, Kai J.; Javidmehr, Alireza; Loge, Frank J.
Abstract: An observed decline in feeding behavior of Delta Smelt Hypomesus transpacificus due to spawning is presented here. At three different temperatures to which examined fish acclimated (10.2, 14.1, and 18.1°C), female Delta Smelt consistently showed significantly higher stomach content than male Delta Smelt when carrying early‐stage eggs. However, a significant decline of feed intake was observed in female Delta Smelt when eggs ripened and were ready for spawning. These results indicate that female Delta Smelt tend to have high food consumption at the egg development stages but change behavior as eggs ripen. Possible causes for the change in feeding behavior are discussed.